2011
DOI: 10.1111/j.1365-2265.2010.03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on maternal hormonal changes in pregnancy

Abstract: An increase in leptin in exercising pregnant women may reflect subtle changes within the placenta in response to regular exercise and may contribute to the reduction in offspring size previously reported in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 37 publications
1
74
1
Order By: Relevance
“…The most consistent reported change in maternal lipids in the acute response to exercise is an increase in triglycerides and free fatty acids compared with the resting state. A longer-term randomized trial of aerobic exercise in the second half of pregnancy in 84 healthy women showed a trend toward lower maternal free fatty acid levels with no change in maternal weight compared with control subjects (42). A trial of postprandial walking (for 20 min after each meal) in women with type 1 diabetes showed a reduction in fasting maternal triglycerides (43).…”
Section: Diet and Exercisementioning
confidence: 99%
“…The most consistent reported change in maternal lipids in the acute response to exercise is an increase in triglycerides and free fatty acids compared with the resting state. A longer-term randomized trial of aerobic exercise in the second half of pregnancy in 84 healthy women showed a trend toward lower maternal free fatty acid levels with no change in maternal weight compared with control subjects (42). A trial of postprandial walking (for 20 min after each meal) in women with type 1 diabetes showed a reduction in fasting maternal triglycerides (43).…”
Section: Diet and Exercisementioning
confidence: 99%
“…Results have varied regarding the effects of maternal exercise on birth weight, though differences may be reported the weights are still within normal birth weight range (Sternfeld et al 1995;Hopkins et al 2011). To begin with, some research shows no change in birth weight regardless of exposure or not to maternal exercise (Collings et al 1983;Carpenter et al 1988;Rose et al 1991;Hatch et al 1993;Sternfeld et al 1995;Horns et al 1996;Clapp et al 2000Clapp et al , 2002.…”
Section: Birth Weightmentioning
confidence: 94%
“…Though methodology has differed, there seems to be a dose-response relationship between maternal activity level (i.e., energy expenditure, intensity) and infant birth weight (Hatch et al 1993) unpublished data). A possible explanation for these findings is that the decrease in birth weight associated with maternal exercise might be a normalization of birth weight in light of the fact that newborn birth weights have increased across generations (Hopkins et al 2011).…”
Section: Birth Weightmentioning
confidence: 97%
“…A lack of effect of exercise on leptin levels during pregnancy has been shown previously: in a study of aerobic stationary cycling training during pregnancy from 20-to 35-week gestation, there was a significant decrease in birth weight but not body composition in the exercise intervention group with no differences in leptin levels between the exercise and the control arms. 30 Another exercise intervention study in women in the US military also reported an increase in leptin levels over the course of pregnancy but no effect of exercise. 34 The leptin levels reported in these studies were lower than in our study, but this likely due to the difference in mean BMI: around 25 versus 35.7 kg/m 2 in our cohort.…”
Section: Leptin Levelsmentioning
confidence: 96%